Evidence of Early Pulmonary Hypertension Is Associated with Increased Mortality in Very Low Birth Weight Infants - Berenz, Andrew; Vergales, Jeffrey E.; Swanson, Jonathan R.; Sinkin, Robert A. (American Journal of Perinatology, 2017)
Objective The objective of this study was to describe the inhospital outcomes of a high-risk cohort of very low birth weight infants with evidence of pulmonary hypertension (PHT) within the first 2 weeks after delivery.Design A retrospective cohort study of consecutively admitted neonates with birth weight < 1,500 g admitted to a Level IV neonatal intensive care unit who were evaluated by echocardiogram between 72 hours and 14 days.Results A total of 343 eligible infants were included in the cohort with a median gestational age of 25.5 weeks and birth weight of 790 g. Evidence of early PHT was associated with birth weight Z-score (odds ratio [OR]: 0.65, confidence interval [CI]: 0.48–0.87) and maternal African American race (OR: 1.9, CI: 1.03–3.69). Early PHT was associated with decreased in-hospital survival compared with those with no evidence of PHT (OR: 2.0, CI: 1.02–3.90), and was associated with an increased rate of moderate-to-severe bronchopulmonary dysplasia at 36 weeks postmenstrual age (OR: 2.92, CI: 1.24–6.89).Conclusion The presence of early PHT on echocardiogram between 72 hours and 14 days of age was associated with decreased in-hospital survival and worse pulmonary outcomes. This population represents a group of infants who warrant further investigation to improve outcomes.
Keywords: pulmonary hypertension; bronchopulmonary dysplasia; preterm; neonate; echocardiogram; patent ductus arteriosus